2019
DOI: 10.1002/ca.23528
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the second through fifth metacarpal through posteroanterior X‐Rays

Abstract: Over the past 10 years, metacarpal fractures have had an annual incidence of 13.6 per 10,000 individuals. Literature has not reviewed anatomical variations through radiographic imaging, which may play a role in reducing postoperative complications. The purpose of this study was to use radiographic imaging to provide a detailed anatomy of the second through fifth metacarpals. This retrospective study measured length, neck width, narrowest body width, and narrowest medullary canal width of the second through fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Although there are many studies concerning the morphometry of human metacarpals, these measurements were generally made using postero-anterior images of dry bone or x-ray radiographs. The literature has shown that the lengths of all metacarpals range between 44.53 and 65.42 mm (Boonyasirikool et al, 2015;Sephien et al, 2020). Wong et al (2018) reported the second to fifth metacarpal bone lengths as 62, 59, 53, and 48 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies concerning the morphometry of human metacarpals, these measurements were generally made using postero-anterior images of dry bone or x-ray radiographs. The literature has shown that the lengths of all metacarpals range between 44.53 and 65.42 mm (Boonyasirikool et al, 2015;Sephien et al, 2020). Wong et al (2018) reported the second to fifth metacarpal bone lengths as 62, 59, 53, and 48 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%